Specificity of personal characteristics of juvenile offenders with different levels of guilt awareness (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The results of the study on the generalisation of psychological characteristics of juvenile offenders with different levels of guilt awareness during their adaptation to the conditions of the educational colony are presented. Based on the theoretical analysis of the philosophical, psychological, scientific and legal literature and the study of legislative acts, the authors characterise guilt as a psychological formation which includes cognitive (assessment of criminal law consequences of a criminal act), behavioural (desire to confess to a crime, to condemn one's actions in front of other convicts, assessment of the likelihood of committing a crime in the future) and emotional (assessment of the attitude towards the crime, its consequences, the victim and the court verdict) components.The personal characteristics of juvenile offenders with different levels of guilt awareness have been determined on the basis of generalisation of empirical studies of emotional and social intelligence, prognostic competence and locus of control as psychological factors of guilt awareness. The empirical part of the study is based on the use of the authors' own and modified methods.Based on the analysis of the components of guilt awareness, the studied adolescents have been divided into three groups: 1) with a high level of guilt awareness (characterised by almost complete guilt awareness); 2) with an average level of guilt awareness (manifested in partial guilt awareness); 3) with a low level of guilt awareness (characterised by the absence or weak guilt awareness).The expediency of using factor analysis to generalise the personal characteristics of juvenile offenders with different levels of guilt awareness has been substantiated. Using this procedure, the latent factors that are significant in the process of assessing the level of guilt consciousness of adolescents have been identified using the principal components method with Varimax raw rotation. Based on the results of the study, the recommendations for the organisation of differentiated psychological and correctional work with each group of juvenile offenders have been formulated. The essence of educational, psychological, correctional and preventive work is the development of personality traits that determine a high level of awareness of guilt for a crime, and all components of the phenomenon under study (cognitive, behavioural, emotional) require attention.